Venezuelan Forced Migrants and Refugees in Brazil and Ecuador: Security Issues and Social Provision during the COVID-19 Pandemic - Andrea P. Pacifico; Johnatan Da Costa Santos; F.L. Silva Silva (Vestnik RUDN. International Relations, 2022)
The worsening economic and social crisis in Venezuela has led to a massive flow of Venezuelan migrants to neighbouring Latin American countries. The influx of forced migrants from Venezuela has challenged the regional security of Latin American countries, which were already experiencing structural and social problems. Brazil and Ecuador, where a significant number of Venezuelan nationals arrived, faced great obstacles in providing the arriving migrants with access to health care and education for their children, jobs, while at the same time meeting the needs and social problems of the local population. After the upheaval of the COVID-19 pandemic in March 2020, social problems such as health, education, job access, security, and governance have proven to be the most challenging in the region. However, as the pandemic situation showed, regional leaders were negligent in their response to the disease and refused to cooperate in addressing the problem, with dire consequences. This article analyses the impact of the Brazilian and Ecuadorian immigration laws and asylum policy on the protection of Venezuelans’ forced migrants and refugees who entered Brazil and Ecuador before and during the COVID-19 pandemic. As a regional security issue, the protection of Venezuelans is the basis for regional stability, which can only be achieved through cross-issue persuasion. The article, therefore, concludes that Brazil and Ecuador, after having created rules and implemented public policies before and after the pandemic, in cooperation or not with diverse international and national actors, to host and integrate Venezuelan citizens in both countries, have followed their commitment in accordance with previously adopted international and regional agreements, and domestic laws.